Measurement of perceived needs in humanitarian contexts using the HESPER scale: a scoping study with reflections on the collaboration between researchers and humanitarian actors - Karin Hugelius (Conflict and Health, 2022)
Abstract Background Needs assessment is one of the fundamental humanitarian responses to sudden-onset or long-lasting emergencies. The Humanitarian Emergency Settings Perceived Needs Scale (HESPER)/ HESPER Web are valid scales for identifying perceived needs among humanitarian or disaster-affected populations, both in humanitarian practice and in science. This scoping review aimed to determine the scientific use of HESPER or HESPER Web, report on previously published perceived needs in humanitarian emergencies, and discuss how scientific and humanitarian actors can work together in a partnership in needs assessment in humanitarian settings. Results In all, eight papers were found in which the HESPER or HESPER Web had been used in conflict- or post-conflict settings or natural disasters. The study samples varied from 85 to 1000 participants (mean 440). The mean number of perceived needs in all studies was 8, varying from 4.25 to 12.18. The top three needs varied in all the studies. A high number of perceived needs was associated with mental health problems. No paper has reported on how the assessment outcomes were shared between the researchers and humanitarian actors. Conclusion Inventorying the needs from the perspective of the affected population is important to tailor the response to each humanitarian emergency. The HESPER scale and the HESPER Web are multisectoral tools that can be used to take inventory of the perceived needs and indicate the mental health problems that arise in conflict-ridden and natural disaster contexts. It is essential that results from a scientific needs inventory are shared with adequate humanitarian stakeholders to not only facilitate a proper response, but also to foster a closer collaboration between scientists, humanitarians, and the affected population. Doing so would increase the development and use of evidence in practice when providing humanitarian aid.